The Effect of Cooperative Learning Model Script and Think-Pair-Share to Critical Thinking Skills, Social Attitude and Learning Outcomes Cognitive Biology of multiethnic High School Students - Didimus Tanah Boleng (Universitas Negeri Malang, 2015)
Pengaruh Model Pembelajaran Cooperative Script dan Think-Pair-Share terhadap Keterampilan Berpikir Kritis, Sikap Sosial, dan Hasil Belajar Kognitif Biologi Siswa SMA Multietnis   Abstract: Biological learning process with multiethnic students requires a learning models which allow students to work independently, to work together in small groups, and to share with other groups. The purpose of this study was to determine the effect of learning models, ethnicity, and the interaction of learning model and ethnic on critical thinking skills, social attitudes, and cognitive achievement. This quasi experimental study was conducted in 11th grade of Natural Science Class Highschool students with six ethnicaly and Junior Highschool National score groups consisted of 132 samples. The results of Covarian Analysis showed that the learning models significantly affected the social attitudes and increased the critical thinking skills and cognitive achievement. Ethnicity significantly affected the social attitudes and cognitive achievement. Interaction of learning models and ethnicity significantly affected students social attitudes. Key Words: cooperative script, think-pair-share, critical thinking skills, social attitudes, biology cognitive achievement, multiethnic students Abstrak: Pengelolaan proses pembelajaran biologi pada siswa multietnis memerlukan model pembelajaran yang memungkinkan siswa bekerja mandiri, bekerja sama dalam kelompok kecil, dan berbagi dengan kelompok lain. Tujuan penelitian ini untuk mengetahui pengaruh model pembelajaran, etnis, serta interaksi model pembelajaran dan etnis terhadap keterampilan berpikir kritis, sikap sosial, dan hasil belajar kognitif biologi siswa. Penelitian eksperimen semu ini dilakukan di kelas XI IPA SMA dengan sampel sebanyak 132 orang siswa terbagi dalam enam kelas yang homogen berdasarkan etnis dan nilai ujian nasional SMP siswa. Hasil analisis data dengan menggunakan Analisis Kovarian menunjukkan bahwa model pembelajaran secara signifikan berpengaruh terhadap sikap sosial dan meningkatkan keterampilan berpikir kritis, dan hasil belajar kognitif; etnik secara signifikan berpengaruh terhadap sikap sosial, dan meningkatkan hasil belajar kognitif biologi; interaksi model pembelajaran dan etnik berpengaruh terhadap sikap sosial. Kata kunci: cooperative script, think-pair-share, keterampilan berpikir kritis, sikap sosial, hasil belajar kognitif biologi, siswa multietnik